Desiccation drives the growth of crystalline graphite in the cold mantle wedge: Evidence from the Achankovil Suture Zone, southern India. (17th January 2021) - Zhang, Cun; Santosh, M.; Yu, Xiaoyan; Rajesh, V. J.
Abstract : Carbon is constantly released from subducting slabs back to the atmosphere in the form of gases such as CO2 and CH4 . This constitutes a source of greenhouse gases that can regulate atmospheric chemistry over geological timescales. However, the carbon carried by hydrothermal fluids released from slabs may be locked along their ascending paths for variably long periods of time. The processes involved in this chromatographic pathway remain unclear. Here we report the co‐occurrence of graphite and phlogopite in highly metasomatized rocks derived from the mantle wedge of a Late Neoproterozoic subduction zone in the Achankovil Suture Zone in southern India. Petrographic, isotopic, and fluid inclusion evidence suggests these rocks formed in an environment soaked in C‐bearing fluids derived from the subducting slabs. We propose that desiccation of slab‐derived fluids in contact with a dry mantle wedge is the main driver for this phenomenon, while redox change only plays a marginal role. Our work provides a perspective on the diversity of non‐traditional carbon graphitization pathways in the lithosphere. It shows that refractory forms of elemental carbon of abiotic origin may be ubiquitous in the cold mantle wedge. Abstract : Mechanism of formation of graphite in a cold mantle wedge.